2013
DOI: 10.1007/s00795-013-0037-9
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistochemical analysis of invasive micropapillary carcinoma pattern in four cases of gastric cancer

Abstract: Gastric cancer with the invasive micropapillary carcinoma (IMPC) pattern has been reported to be a variant with poor prognosis and rapid progression. To the best of our knowledge, only 4 cases of gastric cancer from Japan and 11 cases from Korea have been reported to contain the IMPC pattern. In the present study, 4 cases of gastric cancer containing the IMPC pattern from 2 Japanese men and 2 Japanese women are reported. The cancer tissues, including a recurrent lesion in 1 case and lymph node metastases in 2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 20 publications
1
20
0
1
Order By: Relevance
“…Previous studies have confirmed the presence of these structures in malignancies of the digestive system (9). In addition, it has been demonstrated that the presence of a micropapillary component in tumors indicates aggressiveness and poor clinical outcome (14)(15)(16)(17)(18).…”
Section: Introductionmentioning
confidence: 84%
See 1 more Smart Citation
“…Previous studies have confirmed the presence of these structures in malignancies of the digestive system (9). In addition, it has been demonstrated that the presence of a micropapillary component in tumors indicates aggressiveness and poor clinical outcome (14)(15)(16)(17)(18).…”
Section: Introductionmentioning
confidence: 84%
“…The spaces are separated from one another by thin bands of fibrous tissue and form a structure comparable to a sponge. Nests may also form with fusiform-like cancer cells filling up single spaces (6,7), and are often observed in invasive tumor margins or less frequently in the tumor center (1,(7)(8)(9). The micropapillary structure may constitute one of the morphological tumor components and coexist with other histological types of cancer, or it can be the only morphological feature (3,5,8).…”
Section: Introductionmentioning
confidence: 99%
“…They are also seen in breast [28,29], urothelial [30,31], gastric [32,33] and colorectal carcinoma [34,35]. Two studies reported differences in DNA ploidy in the micropapillary component of urothelial carcinoma [30,31].…”
Section: Discussionmentioning
confidence: 99%
“…Ayrıca ampullo-pankreatikobilier bölgede de İMPK bildirilmiştir (57). Fakat olgu sayısı gastrointestinal İMPK'un immünohistokimyasal profili ve kliniği hakkında bilgi edinmek için yetersizdir (13).…”
Section: Gastroi̇ntesti̇nal Traktta İnvazi̇v Mi̇kropapi̇ller Karsi̇nomunclassified